Chapter 2. Fertilizer Management for Vegetable Production in Florida - Guodong Liu; Eric H. Simonne; Kelly T. Morgan; George Hochmuth; Shinsuke Agehara; Rao Mylavarapu; Craig Frey; Pavlos Tsouvaltzis; Xiaoying Li (EDIS)
Chapter 2 of the Vegetable Production Handbook of Florida